Как поезда под землей оказались? - Малов Владимир Игоревич (Почемучкины книжки, 2016)
Экземпляры: ф.15 (20170920) / Инвентарный номер: 54138 / Цена: / Сис.шифр: 39.81 / Авт.знак: М 19 / ГРНТИ: 73 / ББК: 39.8